2016
DOI: 10.1039/c6ra05995c
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant polymorphs of methoxyflavone (5-methyl-7-methoxyflavone)

Abstract: A novel metastable polymorph and an unstable amorphous phase of methoxyflavone were discovered after a decade since the first report of the X-ray crystal structure of this bioactive compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…If the different nuclei are allowed to grow, different crystal forms are obtained [20,21]. Solvatomorphism formation also depends on the properties of the surrounding environment, such as temperature, humidity and the rate of generation of supersaturation, but the solvent has the most important impact [22].…”
Section: Sxrdmentioning
confidence: 99%
“…If the different nuclei are allowed to grow, different crystal forms are obtained [20,21]. Solvatomorphism formation also depends on the properties of the surrounding environment, such as temperature, humidity and the rate of generation of supersaturation, but the solvent has the most important impact [22].…”
Section: Sxrdmentioning
confidence: 99%
“…Concomitant polymorphs are seen in a variety of molecules. Gong et al found concomitant polymorphs for methoxyflavone, a non-steroidal anabolic isoflavone [20]. Jones and co-workers found Crystals 2024, 14, 99 2 of 16 two concomitant polymorphs of a polyamide molecules, which differ in their hydrogenbonding patterns in the crystal [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we explored the use of crystallization in the presence of additives for minimizing concomitant crystallization that is often observed for pharmaceuticals by studying isonicotinamide (INA) as the model substance. INA is widely used as a common conformer for the cocrystallization of pharmaceuticals and has the potential for pharmacological effects. , INA is reported to crystallize in six polymorphs (corresponding to Cambridge Structural Database (CSD) entries EHOWIH01-06), two monohydrates, and few solvates. INA Form I contains amide homodimers arranged in isolated corrugated sheets .…”
Section: Introductionmentioning
confidence: 99%